2020
DOI: 10.1155/2020/6289392
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum to “Activation of AMP‐Activated Protein Kinase and Extracelluar Signal‐Regulated Kinase Mediates CB‐PIC‐Induced Apoptosis in Hypoxic SW620 Colorectal Cancer Cells”

Abstract: In the article titled "Activation of AMP-Activated Protein Kinase and Extracelluar Signal-Regulated Kinase Mediates CB-PIC-Induced Apoptosis in Hypoxic SW620 Colorectal Cancer Cells [1]," undeclared splicing was identified in the pERK bands, between lanes 5 and 6 in Figure 3(c) and HIF-1 alpha bands between lanes 3 and 4 in Figure 5(a). e authors apologize for these errors which were due to mistakes during the cropping and naming of gels. As the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Various studies have shown that the activation of ERK1/2 and p38 MAPK pathways could induce apoptosis in CRC. 5155 Although the mechanism of combined treatments on ERK1/2 needs to be further elucidated, the p38 MAPK pathway can be activated by TAK1 56 and GADD45A, 57 as is consistent with our findings (Figure 4(a, b, c)). Various studies reported that activation of the p38 MAPK pathway may correlate with SIRT1 activation 58,59 and 5-FU treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Various studies have shown that the activation of ERK1/2 and p38 MAPK pathways could induce apoptosis in CRC. 5155 Although the mechanism of combined treatments on ERK1/2 needs to be further elucidated, the p38 MAPK pathway can be activated by TAK1 56 and GADD45A, 57 as is consistent with our findings (Figure 4(a, b, c)). Various studies reported that activation of the p38 MAPK pathway may correlate with SIRT1 activation 58,59 and 5-FU treatment.…”
Section: Discussionsupporting
confidence: 91%
“…The CA derivative CB-PIC ( Fig. 1 ) has marked cytotoxicity and induces apoptosis in SW620 human colon cancer cells by activating the AMPKα and ERK signaling pathways ( 47 ). Furthermore, CB-PIC is able to overcome drug resistance in chemotherapy cancer cells by inhibiting multidrug resistance protein 1 and its upstream STAT3 and AKT signaling pathways ( 48 ).…”
Section: Antitumor Effects Of Ca In Different Types Of Cancermentioning
confidence: 99%
“…Several molecular mechanisms of action of metformin have been investigated. Based on these studies, proposed potential mechanisms of action include inhibition of the mitochondrial respiratory chain, activation of AMP-activated protein kinase (AMPK), inhibition of glucagon-induced elevation of cyclic adenosine monophosphate (cAMP) and resultant activation of protein kinase A (PKA), inhibition of mitochondrial glycerophosphate dehydrogenase, or an effect on gut microbiota [13][14][15].…”
Section: Review Thiemementioning
confidence: 99%